The role of accounting information in evaluating financing operations in Sudanese banks - a field study - Jafar Hassan Habib, Mohanad (Journal of Research in Finance and Accounting, 2020)
The study examined the role of accounting information in evaluating financing operations in Sudanese banks. Where the study aimed to identify the importance and objectives of accounting information with an emphasis on its importance as a source of information for banks when applying for financing, as well as trying to shed light on the most important factors, determinants and foundations of financing decisions in Sudanese banks. The study reached a number of results, the most important of which was that companies provide accounting information characterized by high-quality qualitative characteristics when requesting financing from banks. Also, modern financial analysis methods contribute to banks in identifying financial risks, which helps in rationalizing financing decisions. The study came out with a number of recommendations, the most important of which was the need for companies to provide banks with immediate information about their activities and performance when applying for granting funding, so that this will be reflected in the decision to grant financing, as well as work to establish institutions and centers specialized in the process of obtaining information, collecting and analyzing data, and assessing the reputation of the applicant for funding.